IMPLEMENTASI KEBIJAKAN PENYALURAN KREDIT DALAM MENGATASI KREDIT BERMASALAH (PT. Permodalan Siak Kabupaten Siak Sri Inderapura) - Suci Romziah; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The study conducted on PT. Permodalan Siak on the road Pangeran No. 12 Siak Sri Inderapura. As for the formulationof the problem, namely how the implementation of credit policies in addressing prolem loans.Population in this study is a costumer. Sampling is done in a way to make the population of the 95 respondents. Data sources of primary data and secondary data. Data collection techniques in this study was a questionnaire. While purposive sampling technique sampling. Method of analys used a single variable, which uses a likert scale to measure the value of each item.The results of this study indicate that the lending policies that include credit requirements, loan guarantees, the implementation of a code of ethics. Costumer assess the policicies implemented have been effective. However, the implementation of the loan application procedures, management of problem loans and credit estimates is still considered effective. To avoid a credit crunch prospective costumerwho have a nutrient guarantee sale. The onlywarraties for initials steps to avoid congestion and the inability to pay the loan installments.Keywords : Lending Policies, PT. Permodalan Siak